Irish Rebellion - Andrews, S. author. aut Link
X, 238 p.
Keywords: The 1798 Rebellion unleashed a paper war involving contemporary historians and pro-Establishment literary reviews. This volume traces this paper-warfare against the background of the Union, Catholic Emancipation, Young Ireland, Gladstone and the Fenians, Victoria's jubilees, the 1898 centenary and the South African War.